2012
DOI: 10.1186/1471-2377-12-162
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and upper extremity function within 72 hours after first occasion of stroke in an unselected population at a stroke unit. A part of the SALGOT study

Abstract: BackgroundReduced upper extremity function is one of the most common impairments after stroke and has previously been reported in approximately 70-80% of patients in the acute stage. Acute care for stroke has changes over the last years, with more people being admitted to a stroke unit as well as use of thrombolysis. The aim of the present study was to describe baseline characteristics, care pathway and discharge status in an unselected group of patients with first occasion of stroke who were at a stroke unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 14 publications
3
107
0
4
Order By: Relevance
“…The higher prevalence of spasticity in the present study may reflect this study's inclusion of all patients with arm paresis at day 3 and the absence of other disease-specific exclusions. Persson et al 2 found that 48% of the total population at a stroke unit had reduced arm function. Because upper-limb spasticity is uncommon in patients with normal arm function, and almost all patients with spasticity have some degree of spasticity in the upper-limb, 10 it may be reasonable to assume that 20%Y25% of all patients with a first stroke will develop upper-limb spasticity during the first year.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The higher prevalence of spasticity in the present study may reflect this study's inclusion of all patients with arm paresis at day 3 and the absence of other disease-specific exclusions. Persson et al 2 found that 48% of the total population at a stroke unit had reduced arm function. Because upper-limb spasticity is uncommon in patients with normal arm function, and almost all patients with spasticity have some degree of spasticity in the upper-limb, 10 it may be reasonable to assume that 20%Y25% of all patients with a first stroke will develop upper-limb spasticity during the first year.…”
Section: Discussionmentioning
confidence: 98%
“…1 Recently, however, a lower prevalence (48%) of arm paresis on hospital admission has been noted. 2 The clinical features of stroke may be categorized as positive (e.g., spasticity) or negative (e.g., muscle weakness). The most commonly used definition of spasticity was proposed by Lance 3 : Bspasticity is a motor disorder characterized by a velocity dependent increase in tonic stretch reflexes (muscle tone) with exaggerated tendon jerks, resulting from hyperexcitability of the stretch reflexes, as one component of the upper motor neuron syndrome.…”
mentioning
confidence: 99%
“…1). At the same time period, there were 642 with stroke who were admitted to at the stroke unit (all from the same catchment region, which has been presented elsewhere (14). This means 4.2% of the stroke population needed neurosurgical care.…”
Section: Characteristicsmentioning
confidence: 97%
“…All patients with first-time stroke at Sahlgrenska University Hospital between February 2009 and December 2010 were identified (as part of the SALGOT study (13,14)), and all who were treated at the neurosurgical department were included. As common, those admitted to neurosurgery were those where a surgical intervention was discussed and where the possible benefits were considered greater than the risk of harming.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation